2003
DOI: 10.1016/s1054-139x(03)00100-9
|View full text |Cite
|
Sign up to set email alerts
|

Parental monitoring, negotiated unsupervised time, and parental trust: the role of perceived parenting practices in adolescent health risk behaviors

Abstract: Purpose-To compare two different parenting practices (parental monitoring and negotiated unsupervised time) and perceived parental trust in the reporting of health risk behaviors among adolescents.Methods-Data were derived from 692 adolescents in 9th and 10th grades (X̄ = 15.7 years) enrolled in health education classes in six urban high schools. Students completed a selfadministered paper-based survey that assessed adolescents' perceptions of the degree to which their parents monitor their whereabouts, are pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
329
3
31

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(397 citation statements)
references
References 27 publications
(67 reference statements)
34
329
3
31
Order By: Relevance
“…There is a possibility that parents are more protective of girls, because of the traditional values in upbringing of boys and girls, where girls, more often than boys, are taught to be caring and conforming individuals (Fontaine, Carbonneau, Vitaro, Barker, & Tremblay, 2009). There is empirical evidence that it is mainly the trust between parents and their child that is protective in regard to girls' behavioral outcomes, while parents of boys in particular need to be informed of their adolescent children's whereabouts in order to protect them (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003). Boys also seem to be more sensitive to overprotectiveness from parents (Kakihara et al, 2010), which consequently may relate to more involvement in risk behaviors.…”
Section: Adolescent Gendermentioning
confidence: 99%
“…There is a possibility that parents are more protective of girls, because of the traditional values in upbringing of boys and girls, where girls, more often than boys, are taught to be caring and conforming individuals (Fontaine, Carbonneau, Vitaro, Barker, & Tremblay, 2009). There is empirical evidence that it is mainly the trust between parents and their child that is protective in regard to girls' behavioral outcomes, while parents of boys in particular need to be informed of their adolescent children's whereabouts in order to protect them (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003). Boys also seem to be more sensitive to overprotectiveness from parents (Kakihara et al, 2010), which consequently may relate to more involvement in risk behaviors.…”
Section: Adolescent Gendermentioning
confidence: 99%
“…Adolescence is a critical period characterized by physiological and behavioral changes that can be affected by the social environment (Gladwin et al, 2011), Having divorced parents and living in non-standard family structures such as single parent families have been associated with an increased likelihood of risky behaviors among adolescents such as smoking, drinking alcohol, substance abuse, and risky sexual behaviors (Kirby, 2002;Orgilés et al, 2012;Carlsund et al, 2013), There is also evidence that perceived parental support and trust reduce the likelihood of smoking, drinking alcohol and risky Abdulmohsen H Al-Zalabani* sexual behaviors, (Borawski et al, 2003) while mixed results have been reported concerning the relationship between parental support and physical activity (Peterson et al, 2013). Parental supervision and monitoring have been associated with smoking and other risky health behaviors such as consuming alcohol, the early onset of sexual activity and unsafe sexual practices (Mahabee-Gittens et al, 2012;Kaynak et al, 2013;Kalina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the adults, the practitioners' responses tended to be clustered around either 'risk-averse' or 'permissive' constructs, whereas parents' responses tended to contain elements of both, suggesting a somewhat schizophrenic stance: they wanted to keep their children very safe but also to help them develop strong and confident attitudes to risk. This finding might be explained by the fact that, as Borawski et al (2003) point out,…”
Section: Discussionmentioning
confidence: 99%